2022
DOI: 10.33448/rsd-v11i3.26795
|View full text |Cite
|
Sign up to set email alerts
|

Utilização da madeira de Pinus oocarpa e Coffea arábica para a produção de painéis de partículas orientadas (OSB)

Abstract: Os oriented strand board (OSB) são um importante produto de madeira projetado, fabricado através da colagem de partículas strand em camadas cruzadas, sendo amplamente aplicado em construções, embalagens, decks, pisos,      revestimentos de paredes e até mesmo para fins de suporte de carga. Para a produção destes painéis, podemos utilizar de biomassa da agricultura, como resíduos da atividade cafeeira. O objetivo desta pesquisa foi avaliar a composição química da madeira de café e do pinus, bem como as propried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…who reported an average of 6,18 % andBrito et al (2021) who obtained an average of 6,34 %. The higher value is considered ideal, because the lignin contributes to the adhesion mechanisms and may contribute to the bonding process of the panels.Regarding the ash,Santos et al (2022) have found a content of 1,20 % close to the present study. However,Andrade et al (2019) obtained a lower content of 0,20 %.…”
supporting
confidence: 89%
“…who reported an average of 6,18 % andBrito et al (2021) who obtained an average of 6,34 %. The higher value is considered ideal, because the lignin contributes to the adhesion mechanisms and may contribute to the bonding process of the panels.Regarding the ash,Santos et al (2022) have found a content of 1,20 % close to the present study. However,Andrade et al (2019) obtained a lower content of 0,20 %.…”
supporting
confidence: 89%
“…For extractives and lignin, the hydrophobic compounds of low molecular weight in the bean residues presented respective values of 8.16% and 8.13%. The values for lignin were lower than those obtained for soybean residues (22,04%)(Borges et al 2022) and coffee wastes (29,28%)(Santos et al 2022). The values of extractives were lower than those obtained from sugarcane bagasse (19,59%)(Soares et al 2017) and soybean residues (13,69%)(Borges et al 2022).…”
contrasting
confidence: 57%
“…For extractives and lignin, hydrophobic compounds of low molecular weight in the bean residues presented respective values of 8.16% and 8.13%. The values for lignin were lower than those obtained for soybean residues (22.04%) (Borges et al 2022) and coffee wastes (29.28%) (Santos et al 2022). The values of extractives were lower than those obtained from sugarcane bagasse (19.59%) (Soares et al 2017) and soybean residues (13.69%) (Borges et al 2022).…”
Section: Bean Residue Characterizationmentioning
confidence: 57%